Pulsed Field Ablation to Treat Atrial Fibrillation: Autonomic Nervous System Effects - Musikantow, Daniel R; Neuzil, Petr; Petru, Jan; Koruth, Jacob S; Kralovec, Stepan; Miller, Marc A; Funasako, Mortioshi; Chovanec, Milan; Turagam, Mohit K; Whang, William; Sediva, Lucie; Dukkipati, Srinivias R; et al. (JACC. Clinical electrophysiology, 2023)
BACKGROUND: During atrial fibrillation ablations using thermal energy, the treatment effect is attributed to not just pulmonary vein isolation (PVI), but also to modulation of the autonomic nervous system by ablation of cardiac ganglionated plexi (GP). OBJECTIVES: This study sought to assess the impact of pulsed field ablation (PFA) on the GP in patients undergoing PVI. METHODS: In the retrospective phase, heart rate was assessed pre- versus post-PVI using PFA, cryoballoon ablation, or radiofrequency ablation. In the prospective phase, a pentaspline PFA catheter was used in a protocol: 1) pre-PFA, high-frequency stimulation (HFS) identified GP sites by vagal effects; 2) PVI was performed assessing for repetitive vagal effects over each set of PF applications; 3) mapping defined PVI extent to identify those GP in the ablation zone; and 4) repeat HFS at GP sites to assess for persistence of vagal effects. RESULTS: Between baseline and 3 months, heart rates in the retrospective radiofrequency ablation (n = 40), cryoballoon (n = 40), and PFA (n = 40) cohorts increased by 8.9 ± 11.4, 11.1 ± 9.4, and -0.1 ± 9.2 beats/min, respectively (P= 0.01 PFA vs radiofrequency ablation; P= 0.01 PFA vs cryoballoon ablation). In the prospective phase, pre-PFA HFS in 20 additional patients identified 65 GP sites. During PFA, vagal effects were noted in 45% of first PF applications, persisting through all applications in 83%. HFS post-PFA reproduced vagal effects in 29 of 38 sites (76%) in low-voltage tissue. CONCLUSIONS: PFA has minimal effect on GP. Unlike with thermal ablation, the mechanism by which PFA treats atrial fibrillation is mediated solely by durable PVI.
Keywords: Catheter Ablation; Vagus Nerve; fibrilace síní; retrospektivní studie; lidé; nervus vagus; prospektivní studie; Atrial Fibrillation; Prospective Studies; katetrizační ablace; Retrospective Studies; atrial fibrillation; cardiac autonomic nervous system; pulsed field ablation; Humans